El rol de la fiscalia y el procedimiento penal acusatorio - Gordillo Sierra, Freddy Javier (2014)
To date, surely we will have read or heard that the theory of the case is the compass of the litigant , is a map that is designed during the process , is the approach that the prosecutor and the defense attorney makes about relevant criminal acts , the legal grounds that support it and the evidence supporting them . In short, we can say that it is a strategic vision to address the process that allows us to: - Take appropriate decisions in the process . - Warn our weaknesses and those of the other party. To build an excellent and effective speech that meets to convince the judges , it is necessary to exhaust a systematic set of steps, which since ancient times in the works of Aristotle and Cicero , began to be explained. These steps have full force today will guide us to be applied to the various interventions of oral accusatory system . First, we must remember that the purpose of oral argument is to persuade the judge, so to achieve that purpose must be clear . And to achieve that clarity is necessary to examine the steps used to create the oral intervention , as these then lead us to the identification of the structure of the allegations. The steps or stages to be exhausted are: • The invention ( inventio ) : WHAT TO SAY . It has to do with the action and the effect of creating the speech. • The provision ( dispositio ) : WHERE TO SAY . It has to do with the organization, with the construction of the discourse structure . • The expression ( elocutio ) : HOW TO TELL . It has to do with finding the appropriate language. • Memory (Memory) : It has to do with the ability to remember what was going to say. • The practice (praxis ) : It has to do with the fact exercises on the speech that was created to get to pronounce it better. • The design of audiovisual material. It involves the use of means to convey , understand and recall information . • Pronunciation ( pronuntiatio ) . It has to do with the specific action of speaking. The invention is related to the action and the effect of creating the speech. In this first step , the writer or speaker seeks what he'll say . It is the creative part in the production of the allegations , in which to persuade , you must first define the objective or objectives sought with the speech , then look for the information sources will inspire to achieve the intended purpose . The judicial discourse is general purpose and one or more specific objectives, which allow to construct logically be concretized discourse. The overall objective is to persuade, convince. Persuade means to win accession to the thesis or theory of the case in question, it is what you want the audience or make public or decided. Hence the importance in this phase seeks to know the audience, including the judge and convince the jury that you want , this will allow you to adapt to your audience and clarify your goals . It is essential to analyze the audience, because this guide to determine objectives, develop strategies, selecting material support, organize the material and deliver the speech. The target or targets are about concretely what you want the audience to understand, do or decide. Persuasive speeches on each of the parties raises a hypothesis discussed problem solution allows shape the discourse. The process is a contest between competing hypotheses that the judge has the task of settling. For example, the prosecution will seek a declaration that the defendant liable for murder, while the defense, the judge is convinced that the defendant acted in a fair defense. Each claim defines the contents of the speech, so , for this to be effective it is essential that the process of creation is clear about what the Case Theory and the central hypothesis that will defend , what the legal issues are the matter poses , as this will allow us to find the evidence and the reasons that support our theory , discourse organization and then pronounce it with strong fundamentals .